Strawberry fruit quality and production under drought stress conditions. - Aguado, Sara; Rodríguez-Hiraldo, Claudia; Posé-Albacete, Sara; Paniagua, Candelas; Blanco-Portales, Rosario; Muñoz-Blanco, Juan; Quesada-Felice, Miguel Ángel; Matas-Arroyo, Antonio Javier; Mercado-Carmona, José Ángel (My University, 2024)
The increase in temperature and the decrease in water resources predicted by climate change models will directly influence the productivity, ripening rate, and organoleptic quality of fruit crops. Strawberry is an important crop in Spain, Spain being the sixth largest strawberry producer in the world. This crop is particularly susceptible to drought stress; climate change will significantly challenge strawberry production in the short and medium term. This assay aimed to characterize the performance of different strawberry (Fragaria × ananassa, Duch.) varieties under water restriction conditions. For this purpose, potted plants of the cultivars Chandler, Camarosa, Amiga, and Rociera were grown in a greenhouse during the production months under sufficient (3.3 L·m-2·day-1) or deficient (0.5 L·m-2·day-1) irrigation conditions. Vegetative growth of plants under stress conditions decreased significantly in the same proportion in all lines tested. However, water use efficiency, estimated as photosynthetic rate/transpiration rate, increased in water-stressed plants of cv. Chandler. Under drought conditions, a significant decrease in fruit weight and size was observed in all genotypes and in the number of fruits produced per plant. The cv. Rociera showed the most significant decrease in fruit yield, 90%, despite this genotype being the most productive in control conditions. Regarding fruit quality, no differences were observed in firmness, except in the Rociera genotype, which produced firmer fruits under stress conditions. Likewise, water restriction did not affect the concentration of soluble solids except in cv. Amiga, in which this variable was significantly increased. As for color, there were no significant changes in the parameters measured. Experiments are underway to determine transcriptomic differences among the different genotypes subjected to drought conditions.
Keywords: Fresas - Cultivo; Plantas - Tolerancia a la sequía; Drought stress; Strawberry; Fruit quality; Fragaria